2021
DOI: 10.3390/su13137495
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Sustainable Management, Dividend Policy and Chaebol

Abstract: This study empirically examines the relationship between corporate sustainable management (CSM) and dividend policy. Among the various motivations related to dividends, this study examines the relationship between CSM and dividend policy based on the agency and signaling theory. After examining the relationship between CSM and dividend policy, we investigate whether belonging to a large business group (chaebol group) has a significant effect on the relationship between CSM and dividend policy. The analysis per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(74 reference statements)
2
8
0
1
Order By: Relevance
“…The second theory that is closely associated with the relationship between CSP and dividend policy is signaling theory (Bhattacharya 1979). According to this theory, companies use dividend payments to give a positive signal to the market about the expected results of the company (Benartzi, Michaely, and Thaler 1997;Miller and Rock 1985;Oh and Park 2021). Using 115 Indian listed companies over the period of -2012, Seth and Mahenthiran (2022 find that signaling via corporate social responsibility (CSR) and dividends are complementary means of managing stakeholder relations.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The second theory that is closely associated with the relationship between CSP and dividend policy is signaling theory (Bhattacharya 1979). According to this theory, companies use dividend payments to give a positive signal to the market about the expected results of the company (Benartzi, Michaely, and Thaler 1997;Miller and Rock 1985;Oh and Park 2021). Using 115 Indian listed companies over the period of -2012, Seth and Mahenthiran (2022 find that signaling via corporate social responsibility (CSR) and dividends are complementary means of managing stakeholder relations.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In emerging markets with a distinct ownership structure and corporate governance measures, few studies have explored the relationship between CSP and dividend policy and most of them support a positive relationship between CSP and dividend policy (Oh and Park 2021;Saeed and Zamir 2021;Sheikh et al 2021;Trihermanto and Nainggolan 2020). In a recent study, using panel data from 320 listed firms from the top 10 emerging countries for the years 2015-2019, Lucas (2020) confirmed that there is a positive impact of sustainability on dividends, indicating that all the interests of stakeholders and shareholders can be aligned.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Dividend decision-making is not mandatory, but it remains a basic and traditional way for investors to generate a return on investment. Therefore, dividend policy can be a social responsibility attitude towards investors (Oh & Park, 2021). The size of the company as a strong determinant of the company's dividend payment decision because larger companies often have easier and better access, so they can raise funds faster to increase their social responsibility activities in the hope of encouraging a positive image and company reputation so that it can make it easier for companies to enter the capital market and will attract many investors (Abu Siam et al, 2021).…”
Section: Introductionmentioning
confidence: 99%